Field Evaluation of Brri Usg Applicator in Dry and Wet Season of Rice Cultivation - Hossen, MA; Rahman, MA; Zaman, MK; Islam, MM (Bangladesh Rice Journal, 2017)
BRRI (Bangladesh Rice Research Institute) USG (Urea super granule) applicator was developed to apply USG in non-oxidized zone at 6-10 cm depth from surface at desired spacing to maintain the recommended USG fertilizer doses of 118 and 168 kg ha-1 during Aman and Boro season, respectively that could be maintained with the adjustment of the applicator for 20 × 20 cm transplanting spacing. It was designed and fabricated with an adjustable facility for two rows operation in the rice field at spacing of 18 × 20, 20 × 20 and 22 × 20 cm. The modified USG applicator tested in the BRRI regional stations (RS) during Aman 2011 and the farmers fields during Boro 2012 season. Walking speed directly influenced the field capacity of the applicator. Walking speed during field operation of the applicator depends on the soil type, USG placement time and puddled condition of the soil and it was varied 2.46-3.72 km hr-1. Field capacity was observed 0.13 and 0.14 ha hr-1 during Boro and Aman season, respectively whereas manual USG application capacity was observed about 0.02 ha hr-1. The depth of USG placement by the applicator (6.01-6.32 cm) was found more compared to manual application (5.61-5.75 cm). The yield performance of USG plots was identical in all locations during both the seasons either applied by hand or by machine. However, in some cases, USG gave significantly higher grain yield compared to prilled urea applied by hand broadcasting method.Modified BRRI USG applicator saved urea fertilizer, ensured proper placement of USG in subsurface zone and reduced drudgery without sacrificing grain yield. Bangladesh Rice j. 2016, 20(2): 49-59